2012
DOI: 10.1016/j.phrp.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli Outbreak and its Incubation Period: Is it Short or Long?

Abstract: ObjectivesThe aim of this study is to determine the incubation period of enteropathogenic Escherichia coli (EPEC), which creates several outbreaks in a year in South Korea.MethodsWe reviewed all water and food-borne outbreaks data reported to the Korea Centers for Disease Control and Prevention (KCDC) from 2009 to 2010 and determined their characteristics. Through this process, we can presume the incubation period of EPEC among outbreaks in South Korea.ResultsA total of 497 water and food-borne outbreaks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…The medium incubation period was 56 h, which is longer than that reported here (Hedberg et al, 1997). In South Korea, the EPEC outbreaks reported from 2009 to 2010 had a short mean incubation period of 12 h (Lee et al, 2012), which was similar to the medium incubation period of 19 h in this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The medium incubation period was 56 h, which is longer than that reported here (Hedberg et al, 1997). In South Korea, the EPEC outbreaks reported from 2009 to 2010 had a short mean incubation period of 12 h (Lee et al, 2012), which was similar to the medium incubation period of 19 h in this study.…”
Section: Discussionsupporting
confidence: 78%
“…The most common symptoms of EPEC cases were diarrhea, followed by abdominal pain and nausea (Lee et al, 2012). In May 2013, an outbreak of diarrheal illness was reported in a high school in Incheon, South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of EPEC from diarrheal patients has been also reported in East Asia. In South Korea, EPEC has caused a total of 26 diarrheal outbreaks during 2009-2010, affecting 1,791 human patients [ 21 ]. A high incidence of EPEC in diarrheal patients has been reported in Japan [ 22 ].…”
Section: Re-emergence Of Epecmentioning
confidence: 99%
“…It includes several categories of enterotoxigenic, diffuse adherent, enteropathogenic, enterohemorrhagic, enteroaggregative, enteroinvasive, and extraintestinal pathogenic E. coli. [25,26] In order to provide further detailed information on phenolic compounds and antibacterial activities of Date Palm (Phoenix dactylifera), the current study was devoted to investigate and compare three different highly consumable varieties of date palm (Phoenix dactylifera) cultivars, namely Ajwa, Khalas Alkharj and Al-Qasim for their broad-spectrum antibacterial effect and phenolic compounds. The current study was carried out to revealed the comparative analysis by experimental evidence in order to provide detailed information on phenolic compounds profiling and antibacterial activities of three different local and highly consumable varieties of date palm (Phoenix dactylifera) cultivars, namely Ajwa, Khalas Alkharj, and Al-Qasim.…”
Section: Introductionmentioning
confidence: 99%